A new titanosaur (Dinosauria: Sauropoda) from the Upper Cretaceous of Velaux-La-Bastide Neuve (southern France). (2nd November 2021) - Díez Díaz, Verónica; Garcia, Géraldine; Pereda Suberbiola, Xabier; Jentgen-Ceschino, Benjamin; Stein, Koen; Godefroit, Pascal; Valentin, Xavier
ABSTRACT: Remains of Garrigatitan meridionalis nov. gen. et sp. were found in two bonebeds of sequence 2 from the upper Campanian site of Velaux-La Bastide Neuve (Aix-en-Provence Basin, Bouches du Rhône department). The vertebrate assemblage is dominated by dinosaurs, including the titanosaur Atsinganosaurus velauciensis. Garrigatitan meridionalis presents three diagnostic characters: hourglass-shaped humeri (proximal and distal thirds of almost the same transversal width) in anterior and posterior views, ilium with a broad rounded hollow slightly posterior to the base of the pubic peduncle, proximolateral margin of the femur only slightly medially deflected. Garrigatitan was a small to medium-sized sauropod (sub/adult individuals between 4–6 metres and 2–2.5 tonnes), showing anatomical differences with Atsinganosaurus, and with the other Late Cretaceous Ibero-Armorican titanosaurs. Large titanosaurian specimens found at Velaux-La Bastide Neuve could belong to adult Garrigatitan individuals reaching a body length of at least 12 metres. Histological analysis of long bones shows features similar to other Late Cretaceous European titanosaurs, indicating that all individuals had reached skeletal maturity (presence of an EFS, heavy remodelling HOS 12 to 14). The new taxon is recovered within the clade Lirainosaurinae. Garrigatitan meridionalis increases the diversity of Late Cretaceous titanosaurs within the Ibero-Armorican Island.